Avoiding never events in orthopaedics theatres: a quality improvement project - Bhaskar Amarnath Bhavanasi; Shrikant Kulkarni (BMJ Open Quality)
Never events in the operating room are a surgeon’s nightmare, with an incidence rate of 54%. These events are highly stressful for theatre staff and significantly compromise patient safety. The aim of this project is to avoid never events in trauma and orthopaedic theatres by ensuring that theatre staff adhere to the surgical pause and imaging pause protocols through regular audits.This prospective study was conducted in both trauma and elective orthopaedic theatres. It involved theatre staff members who were not part of the surgical team. The study was designed to take place on random days across different theatres, with the operating team unaware of the audit to ensure genuine behaviour and compliance.The audits focused on observing whether the surgical and imaging pause protocols were followed correctly. These protocols are critical for verifying patient identity, the surgical site, and the specific procedure and confirming the correct imaging is available and reviewed before proceeding. Data collected and corrective actions were implemented when non-compliance was observed, and data on compliance rates were systematically collected and analysed.Preliminary results indicate a substantial increase in compliance with both the surgical and imaging pause protocols, corresponding with a reduction in the occurrence of never events. Theatre staff reported improved understanding and confidence in performing these safety checks The use of external auditors who were not part of the surgical team provided an unbiased assessment of compliance, enhancing the reliability of the findings.In conclusion, the project demonstrates that regular audits, and data collected by non-surgical team staff, significantly improve adherence to surgical and imaging pause protocols, thereby reducing the incidence of never events in trauma and orthopaedic theatres. This approach highlights the importance of continuous monitoring and education in fostering a culture of safety and precision in surgical practice.